Proceedings of the International Conference on Educational Sciences and Teacher Profession (ICETeP 2018) 2019
DOI: 10.2991/icetep-18.2019.17
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Efficacy and Mathematics ability in the Problem Solving Mathematics

Abstract: The problem solving skills are part of learning mathematics and an important component of 21st century education. But students often experience success doing it. The purpose of this study was to determine the relationship between mathematical abilities, self-efficacy and problem solving abilities. This is a result of low mathematical abilities and self-efficacy. The research was a survey. Samples were randomly selected as many as 135 students from whole high school students in the Kota Bengkulu. The research i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…This study also discovered that self-efficacy has a significant effect on problemsolving ability. The findings are in line with previous research showing that selfefficacy has a positive effect on the general academic scores and mathematical problem-solving ability (Amri & Widada, 2019;Sun et al, 2018). This implies that in circumstances where students are faced with a particular problem, the higher their self-efficacy, the more positive their attitude.…”
Section: Main Effects Of Blended Models and Self-efficacysupporting
confidence: 91%
See 2 more Smart Citations
“…This study also discovered that self-efficacy has a significant effect on problemsolving ability. The findings are in line with previous research showing that selfefficacy has a positive effect on the general academic scores and mathematical problem-solving ability (Amri & Widada, 2019;Sun et al, 2018). This implies that in circumstances where students are faced with a particular problem, the higher their self-efficacy, the more positive their attitude.…”
Section: Main Effects Of Blended Models and Self-efficacysupporting
confidence: 91%
“…They are generally not confident in their ability to solve problems, tend to be unwary, and are not careful in writing their answers (Wiginton, 2013). Prior studies have shown that selfefficacy is closely related to learning achievement in mathematics (Amri & Widada, 2019;Arifin et al, 2021). It is also one of the main factors that determines the success of blended learning implementation (Rafiola et al, 2020;Sun et al, 2018).…”
Section: 5mentioning
confidence: 99%
See 1 more Smart Citation
“…It contributes to the believe construction that the task is doable and they can solve the problems, which is the characteristics of self-efficacy [16]. For the long-term goal, the increase in self-efficacy is expected to increase the students' mathematical ability [17]. Therefore, it is recommended for the teachers to consider the sociomathematical norms in conducting mathematics lesson.…”
Section: E Power Rule Strategymentioning
confidence: 99%
“…Problem solving ability is one part of learning mathematics. Problem solving is an important component of comprehensive 21st century education (Amri & Widada, 2019). According to (Wismath, Orr, Zhong, Wismath, & Program, 2014), that Problem solving is also an activity that must be had in daily life.…”
Section: Introductionmentioning
confidence: 99%